2017
DOI: 10.1016/j.psychres.2017.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxytocin pretreatment on cannabis outcomes in a brief motivational intervention

Abstract: Motivational enhancement therapy (MET) is efficacious in reducing cannabis use, yet benefits are generally short-lived. Oxytocin is a hypothalamic neuropeptide that promotes prosocial behaviors and plays a role in drug-related neuroadaptations; as such, oxytocin may enhance the effect of MET on cannabis outcomes. Cannabis dependent adults were randomized to receive MET plus oxytocin (n = 8) or placebo (n = 8). Participants receiving oxytocin showed reductions in amount of cannabis used daily and number of sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Cutoffs were not specified in five trials (Babor et al, 2004;Levin et al, 2011;Hoch et al, 2014Hoch et al, , 2012Stephens et al, 1994). Only five trials used biological matrices other than urinalysis; three pharmacological trials (two inpatient) used blood plasma to quantify THC and cannabinoid metabolite concentrations (Allsop et al, 2014;Johnston et al, 2014;Trigo et al, 2018), and two used hair (Barrowclough et al, 2014) or saliva (Sherman et al, 2017) to confirm self-reported cannabis use during and after treatment.…”
Section: Cannabis Use Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutoffs were not specified in five trials (Babor et al, 2004;Levin et al, 2011;Hoch et al, 2014Hoch et al, , 2012Stephens et al, 1994). Only five trials used biological matrices other than urinalysis; three pharmacological trials (two inpatient) used blood plasma to quantify THC and cannabinoid metabolite concentrations (Allsop et al, 2014;Johnston et al, 2014;Trigo et al, 2018), and two used hair (Barrowclough et al, 2014) or saliva (Sherman et al, 2017) to confirm self-reported cannabis use during and after treatment.…”
Section: Cannabis Use Measuresmentioning
confidence: 99%
“…Post-TX: prior to each follow-up CAT 2 (0) 0 Bonsack et al, 2011;Roffman et al, 1988 Total: 32 2018 ( Allsop et al, 2014;Carpenter et al, 2009;Johnston et al, 2014;Mason et al, 2012;McRae-Clark et al, 2016;Miranda et al, 2017;Sherman et al, 2017;Trigo et al, 2018 2 Joints/cones Bonsack et al, 2011;Gates et al, 2012;Hendriks et al, 2011;Jungerman et al, 2007;Kadden et al, 2007;MTPRG, 2004Brunette et al, 2011Levin et al, 2004 3 Standard cannabis units (defined as 3 cones OR a joint containing 0. (1) Hill et al, 2017;Johnston et al, 2014;Levin et al, 2004Levin et al, , 2013…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…There is some evidence from two small pilot studies in cannabis users that i.n. OXT may be effective at (1) reducing self-reported cannabis use in cannabis-dependent individuals (Sherman et al, 2017), and (2) decreasing stress-induced cannabis craving and dehydroepiandrosterone (DHEA; a stress-related hormone) levels (McRae-Clark et al, 2013). Unfortunately these studies did not examine sex differences even though OXT is sexually dimorphic at the anatomical, neurochemical and behavioral levels (see reviews by Bisagno & Cadet, 2014; MacDonald & Feifel, 2013; Neumann & Slattery, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent small placebo-controlled pilot by Sherman et al (2017) explored the role of oxytocin in enhancing psychosocial treatment for CUD. Oxytocin is a hypothalamic neuropeptide that has a critical role in social cognition and behavior.…”
Section: Oxytocinmentioning
confidence: 99%